The Oxford handbook of religious space - Kilde, Jeanne Halgren 1957- (Oxford University Press, 2022)
How do we understand religious spaces? What is their role or function within specific religious traditions or with respect to religious experience? This handbook brings together thirty-seven authors who address these questions using a range of methods to analyse specific spaces or types of spaces around the world and across time. Their methods are grounded in many disciplines: religious studies and religion, anthropology, archaeology, architectural history and architecture, cultural and religious history, sociology, gender and women's studies, geography, and political science, resulting in a distinctly interdisciplinary collection
Also issued in print: 2022. - Includes bibliographical references and index
Introduction: Thinking about Religious Space: An Introduction to Approaches - Jeanne Halgren Kilde -- - A Little Bit of Evil: Masjid Kufa in Early Twelver Shi'ism - Najam Haider -- - Mediated Spaces of Collective Ritual: Sacred Selfies at the Hajj - Nadia Caidi, Mariam Karim -- - Pre-Columbian and Indigenous Religious Spaces in Mesoamerica - Brent K. S. Woodfill -- - Roman Catholic Sacred Space - Leonard Norman Primiano -- - Protestant Spaces in North America - David R. Bains -- - Eastern Orthodox Spaces in America - Nicholas Denysenko -- - Planetary Identities: Globalization, Climate Change and Meaning-Making Practices - Whitney A. Bauman -- - Sacred Space in 19th Century Cape Town: Mosque, City, Landscape and a Radical Empiricism of the Spatial - Ozayr Saloojee -- - (In)visible Priorities: Epigraphic Power and Identity at a Jordanian State Mosque - David Simonowitz -- - Hermeneutics of Space: Sacred Space - Michael J. Crosbie --
- Decommissioning and Reuse of Liturgical Architectures: Historical Processes and Temporal Dimensions - Andrea Longhi -- - The Impermanence of Religious Space: Three Approaches to Change in the American Religioscape - Jeanne Halgren Kilde -- - Spaces of Roman Religion and Christianity in Late Antiquity - B eatrice Caseau Chevallier -- - The Religious Landscape and its Architecture in Contemporary Europe - Esteban Fern andez-Cobi an -- - Protestant Architecture in Latin America - Rodrigo Vidal Rojas -- - Diasporic Sacred Spaces: The Case of Boundary Making at an American Sufi Shrine - Merin Shobhana Xavier -- - Situating the Dead: Cemeteries as Material, Symbolic, and Relational Space - Avril Maddrell, Brenda Mathijssen -- - Sites of Miracles and other Holy Places: The Santuario de Chimay o as Case Study - Brett Hendrickson -- - Shared Space, Or Mixed? - Robert M. Hayden -- - Urbanism and Religious Space - Paul-Fran cois Tremlett --
- Fundament and Abyss: Public Religion at the Berlin Holocaust Memorial - David L e -- - Conceptualizing Space and Place: Genealogies of Change in the Study of Religion - Juan E. Campo -- - Religious Spaces as Tourist Sites in Ghana - Alice Matilda Nsiah -- - Exploration of Religious Spaces in Western Africa: Combining Approaches to Understand Spaces - Daniel Dei -- - Women's Mosques: Spaces to Rethink Gender and Religious Authority - Irum Shiekh -- - Visualizing Himalayan Buddhist Sacred Sites in 3D/VR: Pedagogy and Partnership - Lauren Leve, Bradley Charles Erickson -- - Mapping the Spiritual Baptist Universe: Black Atlantic Cosmography and the Spatiality of Spirit in Trinidad and Tobago - Brendan Jamal Thornton -- - Whose Place Is it? Layers of Community and Meaning in the Land of Shinto and Power Spots - Caleb Carter -- - Remnants of Israel: Jewish Spaces and Landscapes in Medieval and Early Modern Europe - Barry L. Stiefel, Jessica Renee Streit --
- Religious Place/Space in Premodern China - Wei-Cheng Lin -- - National Treasures vs. Alien Species: Religious Spaces, Raccoons, and National Identity in Contemporary Japan - Barbara R. Ambros -- - Form and function in the Ancient Synagogue: Evidence from the Second to Seventh Centuries in Palestine and the Diaspora - Marilyn J. Chiat -- - Presence and Performance: Orthodox Spaces of the Eastern Roman Empire - Amy Papalexandrou
Keywords: Sacred space; Religious facilities; Heiligtum; Kultstätte